AVALIAÇÃO NOS ANOS INICIAIS DO ENSINO FUNDAMENTAL: PERSPECTIVAS DE PROFESSORES DE EDUCAÇÃO FÍSICA (Revista Contexto & Educação, 2021)
ABSTRACT: This article has attempted to identify and analyze the perspectives of Physical Education teacher about the evaluation of the first years of Primary School. The research was guided by the qualitative method of investigative research, based on an exploratory study, in which 30 Physical Education teachers working on the first years of primary education were interviewed. The research has revealed that the teachers, during the Physical Education classes at school, within the evaluation practices, have highlighted conceptual, procedural and attitudinal knowledge, with a predominance of the attitudinal ones in relation to the others. Additionally, they manifested that they relate the evaluation of elements corresponding the matters of body movement in Physical Education classes, involving a know-how of the students tied to the movement, as well as an attainment of this movement, valuing the comprehension, reflection and analysis. The considerations about this whole process have revealed an amplification of meaning and evaluative actions from the Physical Education teachers, which are able to signalize for this field of knowledge, a possible reconfiguration aligned to the presuppositions of the body movement culture.
Keywords: KEYWORDS: Evaluation; Physical Education at school; Primary Education.